2009
DOI: 10.1093/fampra/cmp035
|View full text |Cite
|
Sign up to set email alerts
|

GP-led melanoma follow-up: the practical experience of GPs

Abstract: GP-led melanoma follow-up is feasible and, provided certain concerns can be addressed, GPs are willing to provide it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Concern about lack of time, resources, workload and few advantages for their practice [8,30] ✓ ✓ Concern about reduced reassurance for patients [30] ✓ Concern about GPs limited experience [8,30] ✓ ✓ Benefits Potential to improve convenience and continuity for patients [30] ✓ ✓ Potential for greater involvement by GPs in melanoma care [30] ✓ Potential for increased knowledge and skills of GPs [30] ✓ Potential to free up specialists time [30] ✓ Experiences (one study) Positive Comfortable conducting GP-led melanoma follow-up, few reported problems [29] ✓ Importance of training, protocols, recall system and rapid referral pathway to specialists [29] ✓ ✓ Perceived advantage of specialist training/interest in dermatology, but not required [29] ✓ Ideally placed to deliver follow-up care [29] ✓ Minimal disruption of GP practice [29] ✓ GP-led care applicable in all locations, although rural GPs more enthusiastic [29] ✓ Patients' experiences perceived as positive [29] ✓ More efficient use of skin specialist [29] ✓ Negative/concerns…”
Section: Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concern about lack of time, resources, workload and few advantages for their practice [8,30] ✓ ✓ Concern about reduced reassurance for patients [30] ✓ Concern about GPs limited experience [8,30] ✓ ✓ Benefits Potential to improve convenience and continuity for patients [30] ✓ ✓ Potential for greater involvement by GPs in melanoma care [30] ✓ Potential for increased knowledge and skills of GPs [30] ✓ Potential to free up specialists time [30] ✓ Experiences (one study) Positive Comfortable conducting GP-led melanoma follow-up, few reported problems [29] ✓ Importance of training, protocols, recall system and rapid referral pathway to specialists [29] ✓ ✓ Perceived advantage of specialist training/interest in dermatology, but not required [29] ✓ Ideally placed to deliver follow-up care [29] ✓ Minimal disruption of GP practice [29] ✓ GP-led care applicable in all locations, although rural GPs more enthusiastic [29] ✓ Patients' experiences perceived as positive [29] ✓ More efficient use of skin specialist [29] ✓ Negative/concerns…”
Section: Requirementsmentioning
confidence: 99%
“…Maintaining adequate level of expertise if patient numbers small [29] ✓ ✓ Consumption of limited resources [29] ✓ Workload and increased potential for transfer of other tasks to GPs in future [29] ✓ GP on leave when patient recall letter sent out [29] ✓ Patients introducing other matters to follow-up consultation [29] ✓ Patients pre-empting melanoma follow-up as part of consultation on other matters [29] ✓ Adherence (one study)…”
Section: Requirementsmentioning
confidence: 99%
“…The proportion of melanoma follow-up conducted as shared care is currently unknown. And while GP and patient experiences of shared care in melanoma follow-up have been described [26,27], no studies have examined shared care from the perspective of melanoma clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis was based on the small subset of articles (n=14) that included a comparison of surveillance practices by physician specialty. Recommendations for both surveillance intervals and diagnostic imaging and laboratory evaluations varied by specialty [26, 33, 36, 45, 5055]. The greatest variation was seen with respect to recommended frequency of follow-up visits for patients with stage I disease, which ranged from 2 to 4 times per year.…”
Section: Resultsmentioning
confidence: 99%
“…Self-examination was a universal recommendation from every country [21, 34, 41, 42, 48, 49, 5966] and by all practitioner specialties [33, 51, 52, 54, 55, 62, 6770] Surveillance recommendations varied the greatest for patients with stage I disease. Recommended imaging and laboratory evaluations were most intense in the United Kingdom and most minimalist in The Netherlands.…”
Section: Discussionmentioning
confidence: 99%